PENGARUH PROPOLIS TERHADAP KOLAGENISASIPADA PROSES PENYEMBUHAN LUKA SUBKUTAN PUNGGUNG MENCIT YANG DIINDUKSI BAKTERI ACTINOBACILLUS ACTINOMYCETEMCOMITANS - Asdar Asdar (DiscoverSys Inc., 2002)
Propolis, the resinous hive product by bees, is important in the defence of the hive. It is know that extract of propolisexhibits such pharmacological activities as antimicrobia,antiviral, antifungal, anti-inflamatory, immunostimulatoryand promote wound healing. The objective of this studywas to investigate the influence of the propolis on theformation of collagen in the wound healing process of thesubcutan injury of mice that were induced withActinobacillus actinomyctemcomitans (A.actinomyctemcomitans)Thisstudyapplied 24 female BALB/c mice of 2 - 3 monthsof age with the weight of 20 -30 grams. On the first day thewhole population were injected withA.actinomyctemcomitans subcutanly. The second day micewere randomly devided into two groups that was the groupwith special treatment and the controlled ones. The groupunder treatment were given the extract of propolis 100mg/kg body weight every day. While the controlled oneswere only given aquades.Histological observation was conducted upon each groupon the third, seventh and fourteenth days after A.actinomyctemcomitans injection. There-suits of theobservation was based on the density collagen fiber. Thedata obtained then analyzed by using Mann-Whitney U test.The results of the present study indicated that theadministration of 100 mg/kg BWpropolis peroral maystimulate collagen synthesis.